2022
DOI: 10.1613/jair.1.13509
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Machine Learning Techniques for Predicting Match Results in Team Sport: A Review

Abstract: Predicting the results of matches in sport is a challenging and interesting task. In this paper, we review a selection of studies from 1996 to 2019 that used machine learning for predicting match results in team sport. Considering both invasion sports and striking/fielding sports, we discuss commonly applied machine learning algorithms, as well as common approaches related to data and evaluation. Our study considers accuracies that have been achieved across different sports, and explores w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…Moreover, decision tree algorithms are more appealing because they are simpler and easier to implement. Furthermore, using other machine learning algorithms is among the top recommendations for future research in the sports analytics field (Bunker & Susnjak, 2022 ). Therefore, we decided to compare the classification performance of C4.5, ANNs and RF.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, decision tree algorithms are more appealing because they are simpler and easier to implement. Furthermore, using other machine learning algorithms is among the top recommendations for future research in the sports analytics field (Bunker & Susnjak, 2022 ). Therefore, we decided to compare the classification performance of C4.5, ANNs and RF.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, there is a need for more accurate models (Haghighat et al, 2013 ; Bunker & Thabtah, 2019 ). Moreover, even though Artificial Neural Networks (ANNs) are the most commonly used machine learning algorithm in sports analytics, they do not consistently perform better than other techniques (Bunker & Susnjak, 2022 ). In fact, decision tree algorithms are the second most commonly used technique, but they are more appealing than ANNs because they do not generate black-box models which makes them more likely to be implemented (Bunker & Susnjak, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the studies indicated, it was clear that computers and especially machine learning (artificial intelligence) techniques could be used at many points that require experience from the choice of the athletes to the training load and the estimation of their degrees. Today, it is seen that ML techniques are used in many areas of sports, from predicting results in team sports (Bunker and Susnjak, 2022), to athlete health and injury prevention (Eetvelde et al, 2021). Despite the popularity of ML techniques in sports sciences recently, any study has been found in which ML techniques are used for prediction and modeling in the field of the long jump.…”
Section: Introductionmentioning
confidence: 99%